Dipeptide tyrosyl-leucine exhibits antidepressant-like activity in mice - Mizushige, Takafumi; Uchida, Tomoki; Ohinata, Kousaku (Scientific reports, 2020)
Depression is a worldwide health problem. In the present study, we found that a dipeptide, tyrosyl leucine (Tyr-Leu, YL), administered orally, intracerebroventricularly, or intraperitoneally exhibited a potent antidepressant-like activity in the forced swim and tail suspension tests in naïve mice. YL increased the amount of cells expressing c-Fos, a marker for neuronal activity, in the dentate gyrus of the hippocampus. YL increased bromo-2′-deoxyuridine-positive cells and doublecortin expression in the dentate gyrus of the hippocampus, suggesting that YL enhanced the proliferation of hippocampal progenitor cells in vivo and in vitro . YL did not affect hippocampal mRNA and protein expression of BDNF, which is a regulatory factor of both neurogenesis and depression-like behavior. Intriguingly, YL suppressed activation of the hypothalamo-pituitary-adrenal axis by forced swim stress. Moreover, other aromatic amino acid-leucines, Phe-Leu and Trp-Leu, also exhibited antidepressant-like activities, suggesting that the structure of aromatic amino acid-leucine may be important for antidepressant activity. In addition, bovine milk casein-derived peptide, Tyr-Leu-Gly (YLG), an anxiolytic peptide, exhibited an antidepressant-like activity. Our findings demonstrate that YL exhibits an antidepressant-like effect, moderates the stress response, and induces hippocampal neuronal proliferation through a signal pathway independent of BDNF.